The Spiritual Entrepreneur of The Santri Based On Falsafah Local Wisdom Gusjigang In The City of Kudus - Bayu Tri Cahya; Saidatul Munawwaroh; S Surepno; Irsad Andriyanto (Al Tijarah, 2021)
The Kudus Regency society is known as the santri's merchant is so persistent, skilled, and hardworking. The personage of Sunan Kudus is characterized as waliyul Ilmy and this Guardian teaches a philosophy "gusjigang" with a good typology core moral, intelligent of religion and good at trading. The teachings of Gusjigang for the trader's life were able to raise a distinctive characteristic that formed the spiritual value of their daily life. So this research will illustrate the spiritual value of the merchant santri's who are based on the philosophy of local wisdom of Gusjigang in Kudus Regency. The data analysis method used is qualitative with a phenomenology approach and data collection using interviews, observation, and documentation techniques. The purpose of the study of this article is to reveal the spiritual value of the merchant santri's based on the philosophy of local wisdom Gusjigang. the study gave a result of the spiritual practice of merchant santri's in the form of Dalail Khairat fasting, fasting sunnah, Tahajud Praying, and Dhuha praying, and Dzikrullah, as well as the relevance of Gusjigang philosophy, to apply to the self the santri's merchant produce a characteristic that is futurist, altruism, Ihsan and philanthropic.